ANALISIS PERILAKU KEUANGAN GENERASI Z DALAM CASHLESS SOCIETY DI WILAYAH KECAMATAN CAKUNG JAKARTA TIMUR - Hera Maysaroh (2021)
The purpose of this study is to determine the effect of financial literacy, lifestyle, and financial technology on the financial behavior of Generation Z in a cashless society in the Cakung sub-district, East Jakarta. The type of data is quantitative data with a population of Generation Z in the Cakung sub-district, East Jakart a. With a sample of 100 generation Z who have used or are actively using cashless/ non-cash transactions withmethods nonprobability sampling. Data was collected through the distribution of questionnaires. The analysis technique uses Partial Least Square (PLS). The results obtained indicate that: (1) Financial literacy has a positive and significant effect on the financial behavior of Generation Z in the Cakung sub-district, East Jakarta, (2) Lifestyle has a positive and significant effect on the financial behavior of Generation Z in the Cakung sub-district, East Jakarta, and (3) financial technology has a positive and significant effect on the financial behavior of generation Z in the Cakung sub-district, East Jakarta.